SURVIVAL ANALYSIS IN THE CHILDREN WITH SEVERE THERMAL INJURY TRANSFERRED TO THE HOSPITAL WITHIN THE FIRST 72 HOURS AFTER THE INJURY - A. U. Lekmanov; D. K. Azovskiy; S. F. Pilyutik (Вестник анестезиологии и реаниматологии)
The tragic statistics reflecting lethality and survival in children with burns have significantly changed over the last 70 years. A retrospective, non-randomized trial was performed aimed to detect factors providing an impact on survival in a pediatric burns center (1382 children at the age from 0 to 18 years were enrolled in the trial). The inclusion criteria were thermal injuries with hot liquid or flame of more than 20% of the total body surface area, and the area of 10-20% including eyes, ears, face and extremities. The patients were admitted to the intensive care wards of Speransky Children Municipal Clinical Hospital no.9, during the first 72 hours after thermal injury for the period from January 1, 2009 to December 31, 2017.The survival was analyzed using the log-rank test, Kaplan – Meier curves, and Cox regression analysis, and the results demonstrated the significance of the number of factors: early transfer of pediatric patients to a special unit, thermal inhalation injuries, ≥ 12 scores as per ABSI scale, and female gender. The tender age is not one of the factors providing the impact on the survival of such patients.